DAMPAK PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KOMPETENSI PROFESI TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA BIDANG KEAHLIAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Armiati, Armiati; La?ia, Hestu Tansil (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
This study discusses professional competency-based mathematics learning tools for vocational high school students. The purpose of this study is to produce a mathematics learning tool that refers to the field of communication and network engineering expertise, as an effort to overcome the difficulties faced by vocational school teachers in teaching mathematics. The research is a development research that refers to the development of the Plomp model with three stages, namely the preliminary research stage, the design stage and the assessment stage. In this article the results of the assessment phase will be discussed which examines the impact of devices that have been developed on students' problem solving abilities in the field of information and communication engineering. The results obtained are an increase in students' problem solving skills that can be seen in improving the ability to understand the problem, linking the problem with the concept that has been learned, setting a solution strategy, using the strategy, checking back and summarizing the results. This ability is highly needed by vocational school students, because in their work they will face many problems that require all of these abilities. Another visible impact of student activities is an increase in student learning activities as indicated by the willingness and perseverance in completing a given task.